Organizational Management of Teenage Red Cross (PMR) Mula Level in Public Elementary School No.067951 Medan - Aissyahkila Nazwa Dalimunthe; Rizqina Katsiroh Hasibuan; Afni Rahma Sagita Panjaitan (PT PUSTAKA CENDEKIA PUBLISHER, 2024)
Management is one of an organization's management in directing and mobilizing human resources to achieve certain goals effectively and efficiently. Therefore, the application of management needs to be implemented in an organization that can improve the ability and quality of human resources to adapt in the era of globalization. This study aimed to analyze the implementation of PMR extracurricular activities at SD Negeri No.067951 Medan. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis through stages: data collection, data reduction, data presentation, and conclusion drawing/verification. The results showed that PMR Extracurricular Management at SD Negeri No.067951 MEDAN was carried out by applying management functions, namely: PMR extracurricular planning, PMR extracurricular organization, PMR extracurricular implementation, and PMR extracurricular evaluation, effectively becoming a means to foster good values for students, as well as a coaching medium that can support the development of the abilities, interests and talents of students and become a provision for the progress of the field of Red Cross students in the future.